2020
DOI: 10.21203/rs.3.rs-45937/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimation of Effective Reproduction Numbers for COVID-19 using Real-Time Bayesian Method for India and its States

Abstract: WHO declared the outbreak of the novel Coronavirus, COVID-19, as a pandemic on 11th March. On 24th March, a three-week nation-wide lockdown has been announced, which is now extended till 31st May. Effective Reproduction Number (Rt) helps in understanding how effective preventive measures have been in controlling an outbreak. This study assesses the impact of nation-wide lockdown in slowing down the spread of the COVID-19 at the national and state level. An attempt has also been made to examine the important st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Another similar study was done by Tyagi et al in [18] where they concluded to have predicted the number of COVID-19 cases till end of month June and predicted the requirement of ICU beds, ventilators and isolation beds in India using ARIMA(1,3,1) model. The main objective of their work was to predict the medical requirement (ICU 10% of the Active cases, BEDS, Ventilators for 5% of the active cases and isolation bed).…”
Section: Related Workmentioning
confidence: 79%
“…Another similar study was done by Tyagi et al in [18] where they concluded to have predicted the number of COVID-19 cases till end of month June and predicted the requirement of ICU beds, ventilators and isolation beds in India using ARIMA(1,3,1) model. The main objective of their work was to predict the medical requirement (ICU 10% of the Active cases, BEDS, Ventilators for 5% of the active cases and isolation bed).…”
Section: Related Workmentioning
confidence: 79%
“…Our forecasts show an alarming situation for India in the future. In coming months, the actual numbers can go higher than our forecasts of confirmed cases, active cases and healthcare infrastructure as migrant workers are returning home in large numbers currently in large numbers (Tyagi et al , 2020). Currently, India has lifted lockdown with restrictions applying only on the containment zones.…”
Section: Discussionmentioning
confidence: 96%
“…Several previous studies have estimated R e for various scenarios. The effective reproduction number for COVID-19 of India and its states has been determinated in [47] using Real-Time Bayesian Method. [48] determines the effective reproduction number for COVID-19 at the first 10 days of Latin American countries where the highest was in Ecuador(R e = 3.95) and the smallest in Peru (R e = 2.36) and make a comparison with one of Spain(R e = 2.9) and Italy(R e = 2.83).…”
Section: Basic Reproduction Number and Effective Reproduction Numbermentioning
confidence: 99%